2013
DOI: 10.1371/journal.pone.0059430
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition Using Sparse Representation-Based Classification on K-Nearest Subspace

Abstract: The sparse representation-based classification (SRC) has been proven to be a robust face recognition method. However, its computational complexity is very high due to solving a complex -minimization problem. To improve the calculation efficiency, we propose a novel face recognition method, called sparse representation-based classification on k-nearest subspace (SRC-KNS). Our method first exploits the distance between the test image and the subspace of each individual class to determine the nearest subspaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Twenty six images divided in two sessions were captured from each person. The same experiment protocol of Mi et al [53] , [54] was used and for each individual 7 images from the first session without any occlusion were used for training, while the 7 correspondent images from the second session was used for testing. Table 8 shows that the CANet achieves the highest recognition rate in comparison with the methods presented by Mi et al [53] , [54] such as Linear Regression-based Classification (LRC), Robust Linear Regression-based Classification (CLRC) and Sparse Representation-based Classification on K-Nearest Subspace (SRC-KNS).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty six images divided in two sessions were captured from each person. The same experiment protocol of Mi et al [53] , [54] was used and for each individual 7 images from the first session without any occlusion were used for training, while the 7 correspondent images from the second session was used for testing. Table 8 shows that the CANet achieves the highest recognition rate in comparison with the methods presented by Mi et al [53] , [54] such as Linear Regression-based Classification (LRC), Robust Linear Regression-based Classification (CLRC) and Sparse Representation-based Classification on K-Nearest Subspace (SRC-KNS).…”
Section: Methodsmentioning
confidence: 99%
“…For SC+RC, SDC+RC and SSGL+RC, we use the results from SC, SDC and SSGL as the initial values forĝ 0 , respectively. CDR is obtained after solving the problems in (14) and (15) iteratively.…”
Section: A Cup-to-disc Ratio Computationmentioning
confidence: 99%
“…A decimal score is obtained for cataract grading by solving the problems in (14) and (15) iteratively. A ceiling operation is further applied to get the integral grading score.…”
Section: B Cataract Gradingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to [7], the authors argued that for the linear regressionbased classifiers, such as sparse-representation based classification (SRC), features extracted linearly, including the above mentioned ones, have little difference among them. In other words, even we use very simple feature extraction method as downsampling, it is highly possible that the recognition results are equal to the cases that very complicated linear features are used [8,9]. Therefore some studies suggested that for face recognition issue more attention should be paid to design high robust classifier since simple linear features are competent [10][11][12].…”
Section: Introductionmentioning
confidence: 99%